Food allergy in children - Baral, V (BMJ Group, 2005)
Food allergy is being increasingly recognised with the highest prevalence being in preschool children. Pathogenesis varies so diagnosis rests on careful history and clinical examination, appropriate use of skin prick and serum-specific IgE testing, food challenge, and supervised elimination diets. A double blind placebo controlled food challenge is the gold standard diagnostic test. Avoidance of the allergenic food is the key towards successful management. IgE mediated food allergy may present as a potentially fatal anaphylactic reaction, and management consists of the appropriate use of adrenaline (epinephrine) and supportive measures. Sensitisation remains a key target for intervention. Disease modifying agents are currently under trial for managing difficult allergies. Management requires a multidisciplinary approach and follow up.